Study on the Presence of Microplastic in Silowo Ecotourism Waters, Tuban Regency, East Java - Ula, Rahmah Arfiyah; Indahsari, Merinda Nur; Wahidah, Fita Fitriatul; Erviani, Lilik; Ilmiah, Sitti Nur; Ulya, Innarotul (Universitas Pattimura, 2025)
Silowo Ecotourism is one of the water-based recreational facilities that offers swimming and anthropogenic activities that have recently been operating. The existence of ecotourism Silowo stimulates economic activity for the surrounding residents. The high anthropogenic and recreational activity ecotourism Silowo initiated this study to determine the presence of microplastic pollutants in these waters including microplastics amounts, microplastics colors, and microplastics types. Sampling was carried out at four stations in the waters of ecotourism Silowo. The identification of microplastics begins with sample preparation, degradation of organic matter with 30% HNO3, density separation using NaCl, and observation under a microscope. The observation results showed that there were microplastics in the four observation stations. Microplastics found are fibers, pellets, fragments, and films. Based on the type, film is the most numerous microplastics in this study, 38 particles. The colors of microplastics found in this study are green, blue, yellow, red, black, brown, white, and transparent. Microplastics in waters can come from anthropogenic activities around the waters as well as tourist activities in the waters, such as swimming.